Răspuns :
3(2x-1)+25=68 | -25
3(2x-1) = 43 |:3
2x-1 =[tex] \frac{43}{3} [/tex] |+1
2x= [tex] \frac{43}{3} + \frac{1}{1} [/tex] ([tex] \frac{1}{1} [/tex] se am plifica cu 3)
2x= [tex] \frac{46}{3} [/tex] |:2
x= [tex] \frac{46}{3} :2[/tex]
x= [tex] \frac{46}{3} * \frac{1}{2} [/tex]
x= [tex] \frac{23}{3} [/tex]
3(2x-1) = 43 |:3
2x-1 =[tex] \frac{43}{3} [/tex] |+1
2x= [tex] \frac{43}{3} + \frac{1}{1} [/tex] ([tex] \frac{1}{1} [/tex] se am plifica cu 3)
2x= [tex] \frac{46}{3} [/tex] |:2
x= [tex] \frac{46}{3} :2[/tex]
x= [tex] \frac{46}{3} * \frac{1}{2} [/tex]
x= [tex] \frac{23}{3} [/tex]